Respostas de Scenedesmus bijugus a nanopartículas de TiO2 em concentrações ambientalmente relevantes - Mariano, Daniela da Silva (2014)
Phytoplankton cells are base of aquatic food webs, so supporting higher trophic levels and helping equilibrium maintenance in such ecosystems. As residues, nano-TiO2 particles reach aquatic environments where they pose risks to the biota. Literature is controversial about the toxicity of nanoparticles to phytoplankton in general and most data obtained so far has been based on nanoparticles concentrations well above those estimated to occur in natural aquatic environments. Because nanoparticles size vary according to its concentrations, and its toxicity and reactivity are largely dependent on its size, investigations of nanoparticles toxicity at environmentally relevant concentrations are important for the understanding of these compounds onto phytoplankton cells. On the contrary, investigations using higher concentrations can be meaningless. This study aimed at investigating the effects of titanium dioxide nanoparticles (nano-TiO2) at environmentally relevant concentrations (5.10-9 to 5.10- 6 mol L-1) on the freshwater Chlorophyceae Scenedesmus bijugus. We present data of a systematic investigation onto the effects of TiO2 nanoparticles to Scenedesmus bijugus focusing on its physiology under controlled laboratory conditions. We evaluated cell density, chlorophyll a concentrations, growth rates, photosynthetic quantum yield of PSII (continue...)